IMPACT EXPLORATION OF CBT COUNSELING TECHNIQUES ON ACADEMIC ANXIETY: A LITERATURE REVIEW AND CLINICAL PRACTICE - ARINI, LARASUCI; KARNELI, YENI; SYARLI, SETIADI (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
This study explores the therapeutic dimensions in group counseling through the lens of psychoanalytic theory, focusing on the processes of socialization and interpersonal learning. A literature review of recent sources, including journal articles, books, and relevant dissertations, was conducted. The findings indicate that group cohesion, catharsis, and socialization play crucial roles in creating a therapeutic environment that supports individuals in addressing intrapsychic conflicts. Group cohesion fosters a sense of safety, while catharsis allows individuals to express repressed emotions. Additionally, the process of socialization and the imitation of positive behaviors from other group members aid individuals in transforming maladaptive behavioral patterns. These findings underscore the importance of leveraging group dynamics in counseling interventions to support personal growth and deeper self-understanding